Combating Child Labor: Incentives and Information Disclosure in Global Supply Chains - Cho, Soo-Haeng; Fang, Xin; Tayur, Sridhar; Xu, Ying (Manufacturing and Service Operations Management, 2019)
Problem definition: We investigate multinational firms’ inspection and pricing strategies to address the challenges of combating child labor in global supply chains. We also examine how several factors (such as information disclosure, goodwill loss, inspection cost, external monitoring by nongovernmental organizations (NGOs), and penalty scheme) affect firms’ incentives to use different strategies to combat child labor. Academic/practical relevance: Nearly 200 million children are engaged in child labor, many in developing countries that are part of the supply base of global manufacturing networks. However, there has been little research on evaluating the impact of firms’ strategies and NGOs’ initiatives on child labor. Methodology: We develop a game-theoretic model based on a two-tier supply chain, in which a multinational firm in a developed country sells the product made by a supplier in a developing country. Results: If internal inspections are economical, a global firm can reduce the incidence of child labor by inspecting the supplier’s use of child labor. Otherwise, the firm can deter the supplier’s child labor employment by offering a sufficiently high wholesale price or simultaneously using internal inspections and a medium wholesale price. The latter strategy should be adopted only when information about the firm’s inspection policy can be informed credibly. This strategy combats child labor more effectively when a higher penalty is levied onto the supplier’s use of child labor. Managerial implications: A multinational firm that adopts a zero-tolerance policy should consider disclosing its effort to combat child labor (e.g., through a social responsibility report), whereas it should take extra caution when using other penalty schemes. NGOs should help raise the firm’s goodwill cost (e.g., through campaigns and consumer education), but they should be careful about helping to reduce the firm’s inspection cost (e.g., by improving a monitoring system). To prevent children from going back to work after initial removal, a sufficient amount of compensation should be provided to those children, especially when firms rely on inspections without paying a high wholesale price to suppliers.